Real estate and globalisation - Barkham, Richard, 1961- (Hoboken, N.J. : Wiley-Blackwell, 2012)
2000 to 2010 was a remarkable decade for real estate. It started with the dot.com bubble and ended with the putative recovery from the Great Financial Crisis. The period in-between featured the world's first coordinated real estate boom and slump. This book is based on a series of briefings on the relationship between macro economic events and real estate markets in the era of globalisation that covered the period. Collectively they offer unique insights, new ideas and practical approaches to real estate economics, grounded in the day-to-day realities of investment, development and fund management operations in a leading international property company.
Foreword -- Preface -- Acknowledgements -- Introduction -- Macro-economics and real estate -- Real estate and recession -- Inflation and real estate -- Retailing and retail property -- Property companies and reits -- Real estate and construction -- Asia -- Real estate returns -- Residential real estate -- Yields -- Appendix: modelling global real estate yields -- Global office markets -- To follow -- Index.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Real estate business; Housing -- Prices; Real property -- Ownership; Immobilier; Logement -- Prix; x; BUSINESS & ECONOMICS -- Real Estate -- General; Housing -- Prices; Real estate business; Real property -- Ownership